Pediatric Anthrax Clinical Management - Bradley, John S. (Pediatrics, 2014)
Anthrax is a zoonotic disease caused by Bacillus anthracis, which has multiple routes of infection in humans, manifesting in different initial presentations of disease. Because B anthracis has the potential to be used as a biological weapon and can rapidly progress to systemic anthrax with high mortality in those who are exposed and untreated, clinical guidance that can be quickly implemented must be in place before any intentional release of the agent. This document provides clinical guidance for the prophylaxis and treatment of neonates, infants, children, adolescents, and young adults up to the age of 21 (referred to as “children”) in the event of a deliberate B anthracis release and offers guidance in areas where the unique characteristics of children dictate a different clinical recommendation from adults.